Pengaruh Health Education Pada Tingkat Pengetahuan Ibu Dalam Pencegahan ISPA Anak Usia Balita Desa Waimital Kecamatan Kairatu - Ira Sandi Tunny; Maryam Lihi; Siti Rochmaedah (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
ISPA is an acute infection that attacks one or more parts of the respiratory tract from the nose to the alveoli, including the adnexa. This disease is the main cause of death for infants and toddlers. The high incidence and mortality due to ISPA in babies is caused by various factors, one of which is the mother's knowledge about ISPA. This research aims to determine the effect of health education on the level of maternal knowledge in preventing ISPA in toddlers, Waimital Village, Kairatu District. This research uses a quasi-experimental method with an individual pre-post test design approach. The research sample was determined using the Slovin formula, totaling 129 respondents. The research instrument used a questionnaire. The Wilcoxon test results showed that 127 respondents' knowledge increased and 2 respondents' knowledge remained the same, and a sig. (2-tailed) 0.000 which means it is smaller than 0.05, so it can be concluded that p value < α (0.000 < 0.05) then H0 is rejected and H1 is accepted, meaning that there is an influence of health education on the mother's level of knowledge in preventing ISPA. It was concluded thatThere is an influence of health education on the level of maternal knowledge in preventing ISPA in children under five in Waimital Village.